Influence of Technology on Business Sustainability in Petroleum Firms in Nairobi, Kenya - Charles Mutisya; Isaac Gachanja (International School for Social and Business Studies, 2024)
Purpose: Sustainability is gaining more interest among several strategic management scholars. Technology provides a disruptive competitive advantage that is essential for businesses to thrive in a difficult environment where rules and strategies change from time to time. There is little competition among the oil marketers in Kenya because the government controls pricing strategy. The study's main aim was to determine the influence of technology on business sustainability in petroleum firms in Nairobi, Kenya. The study was underpinned by dynamic capability theory. This study adopted a descriptive research design in its investigation. Study design/methodology/approach: The study's total population was 60 oil marketing companies in Nairobi. The study selected heads of business development units from each oil marketing company. Since the population was small, a census was adopted because it was the most appropriate approach. The primary data was collected using questionnaires, where standard questionnaires with closed-ended questions were administered to capture important information about the respondents. Simple linear regression was employed to determine the effect of technology on business sustainability in petroleum firms in Nairobi. Findings: Technology had a positive and significant effect on the business sustainability of oil marketing companies. The study concluded that strengthening technology enhances competitiveness and thus results in business sustainability among oil marketing companies. Originality/value: The study recommends adopting improvised technology for all the processes and services of oil marketing companies.